Literary magazine trends - Zierden, Rachel (My University, 2008)
Paper written by Rachel Zierden in the spring semester 2007 at the University of Wisconsin-River Falls for Dr. Jennifer Brantley's English 482 writing seminar class. In this paper, the author discusses literary market trends in fiction and poetry, examines the contributors to major publications, and analyzes how literary magazines have expanded their content to include other areas of artistic expression.
11 p.
Keywords: Literary style; American poetry; Literary publishing; American literature--20th century; Publishers and publishing--United States; American literature; American fiction; Creative writing; Literary analysis; Literary market trends; Literary magazines; Literary content